Effect of Trenched Zirconia Bar on Flexural Strength of IPS-Empress 2 Ceramic - Hamid Kermanshah; Sepideh Soroor Homayoon; Sholeh Ghabraei; Naeim Berijani (Islamic Dental Association of Iran, 2013)
Background and Aim : In the recent years, inlay-retained fixed partial dentures(FPDs)have gained attention due to the preservation of tooth structure and their conservative tooth preparation. The wettability of IPS2 ceramic surfaces can be increased by acid etching enhancingtheir bond to resin cement. High-strength ceramics cannot be etched due to the high resistance of alumina and zirconia. Inadequate bond between the zirconia and resin cement in zirconia-based FPDs leads to unequal stress distribution on the surface and consequent debonding and failure of the inlay-retainer. This study aimed to evaluate the effect of a trenched zirconia bar on the flexural strength of IPS-Empress 2 ceramic core .   Materials and Methods : In this experimental study, 21 ceramic specimens measuring 3x4x25 mm were divided into three groups:   Group 1 was the control group and fabricated from In-Ceram alumina ceramic   Group 2 specimens were fabricated from IPS-Empress 2 ceramic   Group 3 specimens were fabricated from IPS-Empress 2 and had an embeddedtrenched zirconia bar at the bottom   Specimens were subjected to three point flexural test with 15 mm support span at a cross head speed of 0.5 mm/min. The fracture forces were recorded and data were statistically analyzed using ANOVA and Tukey's test. The fracture surfaces were evaluated with an electron microscope .   Results: The flexural strength of specimens was 302.66 in group 1, 187.25 in group 2 and 247.89 MPa in group 3. Flexural strength of In-Ceram specimens was significantly higher than that of IPS2 (P<0.019) but no difference existed between In-Ceram and IPS2 with an embeddedtrenched zirconia bar. Therefore, use of trenched zirconia bar at the bottom of specimens had limited effects on increasing their flexural strength ).   Conclusion : Flexural strength of IPS-Empress 2 specimenswith an embeddedtrenched zirconia bar was equal to that of the other two groups. Although the flexural strength value of the mentioned group was higher than that of IPS-Empress 2 specimens without the bar and lower than that of In-Ceram alumina specimens, these differences were not statistically significant .